2005
DOI: 10.1523/jneurosci.4182-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Infarct Depolarizations Reveal Penumbra-Like Conditions in Striatum

Abstract: Spreading depression-like peri-infarct depolarizations not only characterize but also worsen penumbra conditions in cortical border zones of experimental focal ischemia. We intended to investigate the relevance of ischemic depolarization in subcortical regions of ischemic territories.Calomel We conclude that in focal ischemia, transient peri-infarct depolarizations emerge not only in cortical but also in striatal gray matter, thereby demonstrating the existence of subcortical zones of ischemic penumbra. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
(60 reference statements)
2
18
0
Order By: Relevance
“…We have previously reported that the striatum is dramatically protected by estradiol in female mice following MCAO (Dubal, et al, 2006, Dubal, et al, 2001, Suzuki, et al, 2007), but the exact mechanism is unclear. The dramatic level of neuroprotection we observe in the striatum may be due to estradiol-mediated suppression of spreading depression from the cortex (Umegaki, et al, 2005, Witte, et al, 2000. In addition, a direct effect of estradiol in the striatum has been attributed to the activation of non-classical, membrane-bound estrogen receptors (Xiao, et al, 2003).…”
mentioning
confidence: 77%
“…We have previously reported that the striatum is dramatically protected by estradiol in female mice following MCAO (Dubal, et al, 2006, Dubal, et al, 2001, Suzuki, et al, 2007), but the exact mechanism is unclear. The dramatic level of neuroprotection we observe in the striatum may be due to estradiol-mediated suppression of spreading depression from the cortex (Umegaki, et al, 2005, Witte, et al, 2000. In addition, a direct effect of estradiol in the striatum has been attributed to the activation of non-classical, membrane-bound estrogen receptors (Xiao, et al, 2003).…”
mentioning
confidence: 77%
“…Despite these changes, CSDs do not cause any longlasting structural damage to otherwise healthy brain tissue (Nedergaard and Hansen, 1988). In ischemic brain, however, repetitive waves of depolarization result in stepwise depletion of energy stores and functional as well as structural deterioration of the penumbra leading to an increase of infarcted tissue volume (Ohta et al, 2001;Selman et al, 2004;Hopwood et al, 2005;Umegaki et al, 2005). The deleterious effects of CSDs are believed to be mainly mediated by a lack of compensatory hyperperfusion usually occurring to match the metabolic strain caused by repolarization (Back et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Murphy et al (2008) demonstrated that ischemic depolarizations and increases in intracellular calcium were glutamate receptor independent and suggested that these depolarizations were the major ionic event associated with the degeneration of synaptic structure early after ischemic onset. Notably, persistent depolarizations resembling anoxic depolarization and transient depolarizations resembling recurrent peri-infarct depolarizations emerge not only in cortex, but also occur in striatal gray matter, suggesting that infarct expansion due to peri-infarct depolarization extends beyond the cortex (Umegaki et al, 2005).…”
Section: Peri-infarct Depolarizationsmentioning
confidence: 99%